Enterprise architecture for digital business : integrated transformation strategies - Hazra, Tushar K.; Unhelkar, Bhuvan (Boca Raton, FL : CRC Press, 2021)
Enterprise Architecture (EA) is an essential part of the fabric of a business; however, EA also transcends and transforms technology and moves it into the business space. Therefore, EA needs to be discussed in an integrated, holistic, and comprehensive manner. Only such an integrated approach to EA can provide the foundation for a transformation that readies the business for the myriad enterprise-wide challenges it will face. Highly disruptive technologies such as Big Data, Machine Learning, and Mobile and Cloud Computing require a fine balance between their business and technical aspects as an organization moves forward with its digital transformation. This book focuses on preparing all organizations - large and small - and those wishing to move into them for the impact of leveraging these emerging, disruptive, and innovative technologies within the EA framework.
Business-Driven SOA -- Agility in Digital Business -- Change Management in Digital Transformation -- Discussion Topics -- Notes -- Chapter 3 Strategic Planning for Digital Business -- Planning for a Data-Driven Digital Business -- Digital Business Strategies -- Inputs to Strategic Planning for Digital Business -- Strategy for Digital Transformation -- Focus on Customer Experience -- Objectivity in Developing Digital Strategies -- Elements of Digital Business Strategies -- Strategies Relate Projects to Capabilities to Goals -- Business Capabilities -- Business Strategies and Enterprise Architecture
"An Auerbach Book."
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change -- Technological innovations; Business planning -- Data processing; Big data; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Information Management; COMPUTERS / Information Technology